Strategies for the Control of Heat Diffusion Systems Based on Fractional Calculus - Jesus, Isabel S. (2006)
The concept of differentiation and integration to non-integer order has its origins in the nineteen century. However, only in the second-half of the twenty century appeared the first applications related to the area of control theory. In this paper we consider the study of a heat diffusion system based on the application of the fractional calculus concepts. In this perspective, several control methodologies are investigated and compared, such as the adoption of a Smith predictor structure for the better control of systems with time delays. Several simulations are presented assessing the performance of the proposed fractional-order algorithms.